2007
DOI: 10.1074/jbc.m700644200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Role of Y1 Receptors in the Coordinated Regulation of Bone and Energy Homeostasis

Abstract: (39)), by contrast, Y2 receptors have not been detected on bone. In addition to effects in bone, Y1 receptors have been considered as important regulators of energy homeostasis, consistent with pharmacological evidence from Y receptor agonists and antagonists to stimulate or inhibit feeding (9). Fasting-induced re-feeding is reduced in germ line Y1 receptor knock-out mice (10), and deletion of Y1 receptors in genetically obese ob/ob mice, in which hypothalamic NPY-ergic activity is chronically increased, signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
250
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 185 publications
(277 citation statements)
references
References 38 publications
25
250
0
2
Order By: Relevance
“…(3) Germ-line deletion of Y1 or Y2 receptors produces similar anabolic responses in bone, resulting in a generalized increase in bone mass owing to stimulated osteoblast activity and an increased rate of bone formation. (4,5) However, the mechanism behind the action of the Y1 versus the Y2 receptor on bone differs: Conditional deletion of hypothalamic Y2 receptors recapitulates the phenotype of germ-line Y2 receptor knockout ORIGINAL ARTICLE J JBMR (Y2 À/À ) mice, (5) whereas bone homeostasis is unaltered by hypothalamus-specific deletion of the Y1 receptor. (4) Y1 receptor expression has been demonstrated in osteoblastic cells lining endocortical and trabecular bone surfaces by in situ hybridization on femur sections and also by RT-PCR on RNA isolated from bone marrow stromal cell (BMSC) cultures (6) and primary calvarial cultures, (7) suggesting that the Y1 receptor may mediate effects on bone via direct actions on osteoblasts, whereas Y2 receptors could not be detected on bone cells using these methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) Germ-line deletion of Y1 or Y2 receptors produces similar anabolic responses in bone, resulting in a generalized increase in bone mass owing to stimulated osteoblast activity and an increased rate of bone formation. (4,5) However, the mechanism behind the action of the Y1 versus the Y2 receptor on bone differs: Conditional deletion of hypothalamic Y2 receptors recapitulates the phenotype of germ-line Y2 receptor knockout ORIGINAL ARTICLE J JBMR (Y2 À/À ) mice, (5) whereas bone homeostasis is unaltered by hypothalamus-specific deletion of the Y1 receptor. (4) Y1 receptor expression has been demonstrated in osteoblastic cells lining endocortical and trabecular bone surfaces by in situ hybridization on femur sections and also by RT-PCR on RNA isolated from bone marrow stromal cell (BMSC) cultures (6) and primary calvarial cultures, (7) suggesting that the Y1 receptor may mediate effects on bone via direct actions on osteoblasts, whereas Y2 receptors could not be detected on bone cells using these methods.…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have shown that NPY can inhibit the cyclic adenosine monophosphate (cAMP) response to parathyroid hormone (PTH) and norepinephrine in osteoblastic cell lines, (8,9) whereas more recently it was demonstrated that NPY can inhibit the formation of osteoclast-like cells induced by the addition of isoprenaline to BMSC cultures. (10) In addition, administration of NPY to BMSC and calvarial cultures isolated from wild-type mice markedly reduced cell numbers (4) and markers of osteoblast differentiation. (7) respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the peripheral nervous system, NPY is a constituent of the sympathetic nervous system, co-stored and co-released with noradrenaline during nerve stimulation [2]. Additionally, several sources of NPY have been identified in various cell types including osteoblasts and adipocytes [3,4,5]. Recently, NPY has been shown to regulate bone homeostasis, being involved in processes such as the regulation of bone mass, where it acts both centrally and peripherally [6].…”
Section: Introductionmentioning
confidence: 99%
“…Germ-line deletion of Y1 or Y2 receptor produces similar anabolic responses in bone, resulting in an increase in bone mass owing to activation of osteoblasts and an increased rate of bone formation [4,9]. However, the mechanism underlying the action of the Y1 receptor on bone differs from that of the Y2 receptor: both germline and conditional hypothalamic Y2 receptor knockout mice share the same high bone mass phenotype [9,10] demonstrating that central hypothalamic Y2 receptors are crucial for this process, whereas bone tissue is unaltered by conditional deletion of hypothalamic Y1 receptors [4] indicating a nonhypothalamic control of bone mass.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation